2020
DOI: 10.1590/1678-7757-2019-0100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passive ultrasonic activation on microorganisms in primary root canal infection: a randomized clinical trial

Abstract: Objective:This clinical study sought to evaluate the effectiveness of passive ultrasonic activation (PUA) in eliminating microorganisms in primary endodontic infection (PEI) after instrumentation of root canals using microbiological culture and checkerboard DNA-DNA hybridization.Methodology:Twenty root canals with PEI and apical periodontitis were selected. The root canals were instrumented and then randomly divided into 2 groups, according to the irrigation method: PUA and conventional needle irrigation (CNI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
0
22
1
2
Order By: Relevance
“…The data collected from the seven included studies are summarized in Table 2 . Three studies compared the effectiveness of irrigation activation systems and that of the conventional irrigation system in reducing the bacterial load [ 37 , 41 , 42 ]. Three studies investigated and compared the efficacy of sodium hypochlorite (NaOCl) alone and that of a combination of NaOCl with dual-rinse HEDP (1-hydroxyethane-1, 1-diphosphonate, or etidronate) [ 40 ], BioPure MTAD (mixture of doxycycline, citric acid, and a detergent) and/or chlorhexidine (CHX) [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data collected from the seven included studies are summarized in Table 2 . Three studies compared the effectiveness of irrigation activation systems and that of the conventional irrigation system in reducing the bacterial load [ 37 , 41 , 42 ]. Three studies investigated and compared the efficacy of sodium hypochlorite (NaOCl) alone and that of a combination of NaOCl with dual-rinse HEDP (1-hydroxyethane-1, 1-diphosphonate, or etidronate) [ 40 ], BioPure MTAD (mixture of doxycycline, citric acid, and a detergent) and/or chlorhexidine (CHX) [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data collected from the seven included studies are summarized in Table 2. Three studies compared the effectiveness of irrigation activation systems and that of the conventional irrigation system in reducing the bacterial load [37,41,42].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This finding confirmed that mechanical canal preparation followed by PUA could not consistently render the canals free of bacteria. [ 7 22 23 ] Seventeen S2 samples from R-IHAN were free of bacteria. In Yared et al ., all S2 samples from R-IHAN were negative.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, according to the results of a clinical trial by Orozco et al, there was no significant difference between passive ultrasonic irrigation and conventional irrigation in decreasing bacterial counts. 30 Furthermore, the results of a systematic review by Susila and Minu showed that the utilization of mechanical active irrigation devices is advantageous in root canal treatment. They stated that mechanical active irrigation devices are clinically efficient in the conveyance of the irrigant in the root canal, which leads to more cleanliness in root canals.…”
Section: Discussionmentioning
confidence: 99%